Freestanding Osteolipoma of the Left Upper Extremity: A Case Report - Manuel Rodriguez-Leiva, APRN-BC; Rajshri Shah, MD; Elizabeth Anne Ouellette, MD, MBA (Journal of Hand Surgery Global Online)
A 65-year-old woman presented to clinic with a lump at the dorsal aspect of left distal forearm. On clinical examination an oval, soft tissue mass without pulsation was found at the dorsal aspect of left distal forearm. The diagnosis was a rare osteolipoma found underneath the fascia of the muscles extending all the way down to the interosseous membrane and the periosteum of the radius and ulna. The mass was not connected with the interosseous membrane. Osteolipoma are uncommon but have distinguishing radiological and pathological appearances. It is important to keep this differential in mind when a lesion enclosing fatty tissue with ossification is encountered.